2018
DOI: 10.1111/sms.13031
|View full text |Cite
|
Sign up to set email alerts
|

Force coordination strategies in on‐water single sculling: Are asymmetries related to better rowing performance?

Abstract: Asymmetries of the rowing stroke cycle have been assessed with reference to kinematics and foot-force measures in laboratory testing environments. It remains unclear how asymmetries in propulsive kinetic measures are related to on-water rowing performance. A new approach for the evaluation of both global and local asymmetries across the entire movement was used to assess the continuous role of asymmetries and whether these change according to the level of competitive representation. Twenty-seven highly skilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…This study also found that the relationship between body weight and the ranking of times shows a negative correlation, suggesting that the mass has a significant drag effect in this ranking, corroborating the results of studies 14,15 in which negative correlations were identified with body weight (r= -0.50).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study also found that the relationship between body weight and the ranking of times shows a negative correlation, suggesting that the mass has a significant drag effect in this ranking, corroborating the results of studies 14,15 in which negative correlations were identified with body weight (r= -0.50).…”
Section: Discussionsupporting
confidence: 87%
“…According to Warmenhoven et al, 14 the time and power in the 2000 meters in the rowing ergometer are correlated with the time in the 2000 meters in the individual boat. In another study, Mikulic et al 12 showed a strong correlation in 24 rowers in the junior category, between the ranking of the individual boat times with the 2000 meters time on the rowing ergometer (r= 0.80; p≤0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance or meaning of these patterns can then be assessed relative to a research questions through analysis of fPC scores. These scores are analysed in the same way as other discrete variables and have been used in conjunction with different hypothesis testing techniques 16 (i.e. ANOVAs), multivariate statistical techniques 14,15 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors explain that effective strength coordination throughout the stroke cycle is a significant aspect of performance. [21][22][23] Not only does the current study demonstrate that the highest correlation is found in the third 500 meter split, but also proposes that the greater the power over the 1500 meters of the race, the better the result. Also, particular attention should be focused on speed resistance stimuli, always within the percentage calculations of competitive speed, since the highest correlation occurs in the third split.…”
Section: Discussionmentioning
confidence: 73%